Integral estimates for a class Bn of operators - WALI, Shah Lubna; LIMAN, Abdul (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
Let Pn be the class of polynomials of degree at most n. Rahman introduced a class Bn of operators B that map Pn into itself. In this paper, we establish certain integral estimates concerning B-operator, and thereby obtain generalizations as well as improvements of some well known inequalities for polynomials. Mathematics Subject Classification (2010): 26D10, 41A17.